THE FREQUENCY OF USE OF EEG AND NEUROFEEDBACK IN SPORT, SYSTEMATIC REVIEW - Bíró, Eszter; Balogh, László (Stadium - Hungarian Journal of Sport Sciences, 2021)
Increasing athlete performance is an eternal challenge in the world of sports. The success of the training work performed can be checked by performance diagnostics. Proper brain processing is essential for skill learning and the implementation of effective motor performance. It was important for brain mapping technology to improve the capabilities of imaging devices in order to measure cognitive-motor performance in the field. The primary purpose of this review was to summarize the frequency of applications of EEG and its associated neurofeedback in sport. Examine the differences and characteristics of protocols. Assess whether there is this uniform, standardized protocol for each sport and how often it is used among both elite and amateur athletes. Electroencephalography was initially used most in sports in which the stable setting was followed by only minimal movement. These include sport shooting, archery and golf and baseball. Later, it was possible to analyze more complex movements with EEG, such as cycling. One of the most commonly used techniques is neurofeedback training, but despite some research on the topic, the arena of neurotechnology in sports psychology still exists in its rudimentary form and is constrained by a plethora of technological problems.